Existential psychology and therapy: An outline of human being dilemmas - Kočiūnas, Rimantas (Psichologija, 1996)
The present article describes the main principles of existential psychology and its application to counselling and psychotherapy. The key philosophical reference points of existential psychology and therapy are formulated here. When we speak about the novelty of existential psychology we should mention first of all the idea of the total, indissoluble interrelationship of the individual and his/her world. Each individual and his/her world are said to coconstitute one another. Existential psychology posits after L. Binswanger three different planes of the world that characterize our life as Being-in-the-world: (l) Umwelt - the surrounding world; (2) Mitwelt - the world of other people and relations with them; (3) Eigenwelt – our own world and our relations to ourselves. Another important principle of existential psychology is understanding the individual and his/her life in view of his/her intrinsic ontological characteristics. The main characteristics are finiteness of life (death), anxiety, and guilt. From its very beginnings, existential psychology was not only theorization about the understanding of men, but as a practice of psychotherapy (existential analysis, Daseinanalysis, existential therapy, logotherapy, etc.). The main goal of existential therapy is to help the individual who is looking for help to experience his/her existence as real, authentic, as Being-in-the-world with certain potentialities and certain limitations. Existential therapy is oriented namely towards three main features of authentic existence: (1) towards full awareness of the present situation; (2) towards the choice of how to live in this present situation; and (3) towards accepting responsibility for one's decision. Concerning the work of existential therapists, there are some principle points: the basic attitude of the therapist; the understanding of the client; the relationship between the therapists and the client; encouraging the client to undertake real actions in his/her life. Existential therapy differs from other trends, not because it has some specific techniques and methods, but because it perceives and understands the clients' problems in a specific, existential context, with a specific, existential attitude. In practice, existential therapy deals with the main, inevitable questions of human existence, with existential dilemmas or, what was called by J. Yalom, existential gives or concerns. They are death, freedom, isolation, and meaninglessness. Encounters with them constitute the essence of existential dynamic conflicts. They are the main themes in existential therapy and they create the context of discussing concrete problems of clients.
Keywords: existential psychology; existential therapy; human being dilemmas